Comparison of presentation, treatment and follow-up outcomes in first and second wave cohorts of multisystem inflammatory syndrome in children - Yılmaz, Münevver; Gürses, Dolunay; Oğuz, Merve; Kılbaş, Gülşah; Yüksel, Selçuk (Frontiers in Pediatrics, 2026)
ObjectiveMultisystem inflammatory syndrome (MIS-C) is life-threatening complication of coronavirus disease 2019 (COVID-19) in children. The objective of this study is to compare the clinical features, and follow-up results of MIS-C patients between the first and second waves of the disease.MethodsThis study was conducted retrospectively in children with MIS-C who were hospitalized in Pamukkale University Hospital. The first wave was defined as October 2020-June 2021 and the second wave as August 2021-February 2022. The clinical characteristics of the patients were recorded. The patients were evaluated by echocardiography at the sixth and twelfth months.ResultsSeventy were diagnosed in the first wave and 32 were diagnosed in the second wave, with 102 children included in the study. Pulmonary system involvement was more common in the first wave (p = 0.043). In the second wave, IL-6 (p = 0.033), ESR (p = 0.001), ALT (p = 0.048), LDH (p = 0.009), lipase (p = 0.05), and D-Dimer (p = 0.027) were found higher. Elevated ESR (p < 0.001), LDH (p = 0.038), and ALT (p = 0.008), thrombocytopenia (p = 0.011), and pericardial effusion were more frequent in the second group (p = 0.024). At the 12th month evaluation, it was observed that coronary aneurysm persisted in one patient each in the first and second waves groups.ConclusionsThe findings of this study revealed a significant increase in laboratory parameters of the MIS-C patients in time throughout the COVID-19 waves. There was no significant difference between the cohorts about different waves in terms of clinical findings and treatments. The echocardiographic findings of the patients have also not differed significantly between follow-ups.